(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
"Green Concrete, renowned for its resource-efficient nature, plays a pivotal role in curbing environmental impact, reducing carbon dioxide emissions, and minimizing wastewater production. This study involves a comparative assessment of the strength and durability characteristics between conventional concrete and green concrete, which incorporates recycled coarse aggregates and fly ash. In the laboratory setting, three sets of concrete mixtures were meticulously prepared; adhering to the concrete mix design specified by IS 10262:1982 and IS 456 standards. The findings indicate a marginal decrease in compressive strength (approximately 10 to 12%) and tensile strength in green concrete. This reduction might be attributed to the reduced angularity index of the recycled aggregates utilized. Additionally, there was a notable decrease in the tensile strength, up to 25%, observed in recycled aggregate concrete compared to conventional concrete, possibly due to reduced binding of aggregates in the former. However, the performance of green concrete closely mirrors that of conventional concrete, which can be attributed to the pozzolanic action facilitated by the presence of fly ash in green concrete. Moreover, the study reveals a moderate rate of chloride ion permeability in green concrete with water/cement (W/C) ratios of 0.3 and 0.4. At a slightly higher W/C ratio of 0.5, there is a slightly elevated rate of chloride ion permeability observed in green concrete."